Efficacy and Safety of Chinese Medicinal Herbs for the Treatment of Hyperuricemia: A Systematic Review and Meta-Analysis. (13th October 2016) - Lin, Jianping; Chen, Shaoqing; Li, Shuzhen; Lu, Meili; Li, Yanan; Su, Youxin
Abstract : Background . Chinese medicinal herbs may be useful for the treatment of hyperuricemia, but there has been no systematic assessment of their efficacy and safety. Objectives . To systematically assess the efficacy and safety of Chinese medicinal herbs for the treatment of hyperuricemia. Methods . Six electronic databases were searched from their inception to December 2015. Randomized controlled clinical trials (RCTs) were included. Cochrane criteria were applied to assess the risk of bias. Data analysis was performed using RevMan software version 5.2. Results . Eleven RCTs with 838 patients were included. There was no significant difference in serum uric acid between Chinese medicinal herbs and traditional Western medicine (SME: 0.19, 95% CI: −0.04 to 0.43;p = 0.10 ). In terms of overall efficacy, the Chinese medicinal herbs were significantly superior to Western medicine (RR: 1.11; 95% CI: 1.04 to 1.17;p = 0.0007 ). The Chinese medicinal herbs were better than Western medicine in reducing the adverse reactions (RR: 0.30; 95% CI: 0.15 to 0.62;p = 0.001 ). And all these funnel plots showed unlikelihood of publishing bias. Conclusions . The results indicate that Chinese medicinal herbs may have greater overall efficacy with fewer adverse drug reactions, although the evidence is weak owing to the low methodological quality and the small number of the included trials.